Peran Guru Pendidikan Agama Islam dalam Meningkatkan Kualitas Literasi Membaca Qur'an Siswa Sekolah Menengah Atas - Edi Nurhidin (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: This paper aims to describe the role of Islamic religious education (PAI) teachers in improving the competence in reading the Qur'an of students at Public Senior High School (SMA Negeri) 1 Ngadiluwih Kediri. The research method used is descriptive qualitative with interactive data analysis techniques Miles and Huberman that consist of three steps, those are : data reduction, data presentation, and conclusion. There are two questions raised in this study. First, what is the driving factor of PAI teacher's program the Qur'anic literacy in the learning process? Second, how is the practice of Qur'an literacy in the PAI learning process? The results of this study concluded that there were two main driving factors for pie teachers to study the literacy of reading the Qur'an, (1) Internal factors in the form of curriculum Waka instructions and objective conditions of the ability to read diverse al-Qur'an students; (2) Internal factors, namely experience, and desire of pie teachers. Second, the practice of Literacy takes place in an integrated manner in the process of learning PAI by managing lesson hours and using the Nderes Qur'an method. Therefore, PAI teachers play an important role in overcoming the problem of reading the Qur'anic Literacy experienced by students. Abstrak: Tulisan ini bertujuan untuk mendeskripsikan peran guru pendidikan agama Islam (PAI) dalam meningkatkan kompetensi membaca Qur'an siswa SMAN 1 Ngadiluwih Kediri. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik analisis data interaktif Miles dan Huberman yang terdiri dari tiga hal yakni reduksi data, penyajian data dan penarikan kesimpulan. Ada dua rumusan masalah yang diajukan dalam penelitian ini. Pertama, apa faktor pendorong guru PAI memprogramkan literasi Qur'an dalam proses pembelajaran? Kedua, bagaimana praktik literasi Qur'an dalam proses pembelajaran PAI? Hasil penelitian ini menyimpulkan bahwa ada dua faktor pendorong utama guru PAI membelajarkan literasi membaca Qur'an, (1) faktor internal berupa instruksi waka kurikulum dan kondisi objektif kemampuan membaca Qur'an siswa yang beragam; (2) faktor internal yakni pengalaman dan keinginan guru PAI. Kedua, praktik pembelajaran literasi Qur'an berlangsung secara terintegrasi dalam proses pembelajaran PAI dengan mengelola jam pelajaran dan menggunakan metode nderes Qur'an. Oleh karena itu, guru PAI memainkan peran penting dalam mengatasi problem literasi membaca Qur'an yang dialami siswa.